Resurgence of Sudan Virus Disease (SUVD) in Uganda - Damian Alexander Honeyman; Adriana Notaras (University of New South Wales, 2022)
On September 20th, 2022, a case of ebola virus disease was confirmed in Uganda by the World Health Organization. The presumed index case of a 24-year-old male was sequenced and identified as the Sudan strain. This was the first known outbreak of ebola in Uganda since 2012. At the time of publication, 43 cases have been confirmed, including nine deaths. Of all confirmed, suspected, and probable cases, 63 have been identified, with 29 deaths. The current outbreak has spread across five districts within Uganda. The rapid increase in a short period and the growing list of close contacts make outbreak control difficult. Furthermore, a lack of viable vaccines preventing protection and poor health infrastructure with limited finances seem to contribute to the current outbreak. Whilst the true natural reservoir and how spillover to human hosts occurs remains unknown, these outbreaks of EVD will continue to occur in African countries where the virus remains endemic.